2021
DOI: 10.1016/j.jclinepi.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and testing an index of bias attributable to composite outcomes in comparative studies

Abstract: Background: Little guidance is available on how composite outcomes should be interpreted, especially in situations of varied direction in the association across the event subtypes. I proposed an index to evaluate the bias attributable to composite outcomes (BACO) and applied it in recently published clinical trials.Methods: I defined the BACO index as the ratio between logarithms of the association measures of both a composite outcome and its most relevant component (e.g., any-cause mortality). By using the no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…We included randomized clinical trials where the primary outcome was a binary composite outcome that included all-cause mortality among its components [6].…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…We included randomized clinical trials where the primary outcome was a binary composite outcome that included all-cause mortality among its components [6].…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…In this context, the Bias Attributable to Composite Outcome (BACO) Index is a recently developed strategy that aids in interpreting the effects on a composite outcome [6]. This index corresponds to the ratio of the logarithms of the measures of association between the composite outcome and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BACO index <0, 0 to <1, and >1 indicated that the composite endpoints were inverted, underestimated, and overestimated, respectively. A BACO index of 1 indicates that the composite endpoint usage resulted in unbiased results [40]. The composite endpoint in a clinical trial means the use of multiple endpoints.…”
Section: Composite Endpointsmentioning
confidence: 99%
“…They are designed to capture a greater number of outcome events, and thus increase a trial’s ability to demonstrate a statistically significant treatment effect [ 8 ]. Other proposed methodological benefits include reduced sample size requirements, avoidance of the need to choose a single primary outcome, reduced use of multiple statistical comparisons [ 9 , 10 ] and to account for competing risks [ 11 ]. However, significant limitations have been identified regarding the implementation [ 11 , 12 ] and interpretation [ 8 , 10 ] of COM.…”
Section: Introductionmentioning
confidence: 99%